Toward precision medicine in brain metastases - Bergmeister-Berghoff, Anna Sophie; Brastianos, Priscilla K. (Seminars in neurology, 2018)
Brain metastases (BMs) reflect an area of high clinical need, as up to 40% of patients with metastatic cancer will develop this morbid and highly fatal complication. Historically, treatment strategies have relied on local approaches including radiosurgery, whole-brain radiotherapy, and neurosurgical resection. Recently, targeted and immune-modulating therapies have shown promising responses and have been introduced in the clinical management of patients with BMs. Recent improvements in genomic technologies have enriched our understanding of BMs and have demonstrated that BMs present with significant genetic divergence from the originating primary tumor, such that potentially targetable genetic alterations are detected only in the BMs. However, this genetic divergence also results in genetic alterations associated with resistance to targeted therapies. A deeper insight on the genetic alterations of BMs and the interaction with the brain microenvironment will likely reveal new treatment targets, moving toward more precision therapies for patients with BMs.
Gesehen am 19.06.2019